ANALISIS TENTANG KEBIJAKAN PEMUNGUTAN PAJAK PERATURAN PEMERINTAH NOMOR 46 TAHUN 2013 TERHADAP USNAHA MIKRO, KECIL, DAN MENGANGAH (UMKM) DITINJAU DARI ASAS-ASAS PEMUNGUTAN PAJAK - Annisa Ulul Azmiya; Mohamad Khoiru Rusydi (Jurnal Ilmiah Mahasiswa FEB, 2013)
Indonesia is developing country with the main source for funding comes from tax revenue. The Government Regulation No. 46 Year 2013 was published to maximize national income derived from tax revenue. Many pros and cons when this Government Regulation was published. Based on that, the author conducted this study to analyze the taxation policy on Government Regulation No.46 Year 2013 toward business owners or Small Medium Enterprises (SMEs) whether in accordance with the taxation principles. The taxation principles used on this study consists of the revenue productivity principles, equity principles (horizontal and vertical), and ease of administration principles (certainty, convenience, efficiency, and simplicity). The research approach used on this study were qualitative and descriptive while the data were primary and secondary. Based on the research result, it is known that the taxation policy fulfill revenue productivity, convenience, and simplicity principles but it does not fulfill the certainty, efficiency, equity (horizontal and vertical) principles. Due to the imbalance amongst government and tax payer, the author gives alternative suggestion taxation for SMEs. The alternative suggestion was made to replace one percent taxation from omzet into one percent from net income. Keywords : tax policy, SMEs, the taxation principles